Pengaruh Faktor Sosial Ekonomi Terhadap Pernikahan Dini di Desa Madopolo Kecamatan Obi Utara - Asnita Ode Samili; Jainudin Hasim (Universitas Khairun, 2022)
The problem in this study is the socio-economic factors of early marriage. This type of research is classified as qualitative descriptive with a socio-economic approach. The data sources in this study were early marriage actors, parents of early marriage actors. Data collection methods used were interviews, documentation and reference tracing. Data management and analysis techniques were carried out by conducting in-depth interviews with informants. After the interview, the researcher made the results of the interview by playing back the recording of the interview and then writing down the words that match what was in the recording. After the researcher writes down the results of the interview, the researcher then makes data reduction by means of abstraction, namely taking data that is appropriate to the research context and ignoring data that is not needed. The results showed that the causes of early marriage in terms of the economy in Madopolo, North Obi sub-district were parents' economic factors, educational factors, factors ensuring parental sustainability, family economic dependence, namely helping to ease the economic burden of parents, being responsible for carrying the economic burden, yet economically ready and lead to productive employment.Keywords: Early Marriage, Madopolo Village.